Ketidaktepatan Frasa Alasan Pemaaf Pada Ketentuan Pencemaran Nama Baik Dalam KUHP Nasional - Bagaz Zubaba; Rusmilawati Windari (JURNAL RECHTENS, 2025)
Law Number 1 of 2023 concerning the National Criminal Code as a criminal law reform still contains errors in its formulation. This inaccuracy is demonstrated by the phrase “excusable grounds,” which is interpreted as removing the unlawful nature of the provisions in the explanation of Article 433 Paragraph (3) regarding grounds for criminal exemption in criminal defamation.This is a normative research based on statute, conceptual, and comparative approach. The study conducted generates 2 results “forced to defend oneself” and “for the public interest” should be categorized as justifying reasons and not exculpatory reasons because justifying reasons eliminate the unlawful nature of the act and exculpatory reasons eliminate the offender's guilt/criminal responsibility. Inaccuracies in the formulation should be minimized because they can have implications for the objectives of the criminal provisions and their application. The recommendation of this study is to revise the wording of the article so that it is in line with the principles of criminal law and applicable doctrine, thereby creating legal certainty and justice in the national criminal law system.